Determination of the importance of job offer characteristics by students of economic studies: factor analysis - Wronowska, Gabriela (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The paper addresses the current subject matter related to the students’ activity in the labour market and constitutes a part of the current research trend related to students’ search for employment. Aim: The paper presents four research questions: What is important to students of economic studies in a job? What job offers do students of economic studies look for? Which characteristics of a job offer are important for students of economic studies and why? Is there a difference in the expectations of students of economic studies regarding job offers, which is determined by gender, age, place of residence, type of study and source of income? In order to obtain data, an online questionnaire was developed and filled out by students of the Cracow University of Economics (N=756). The search for employment is based on individual preferences, but the survey can identify those that are common to the surveyed group of students. In order to analyze the collected data the Factor Analysis was implemented, with-in which the Principal Components Analysis method was used. The rotation method and the scree criterion were used to determine the number of factors. Next, the factor analysis was used to show the differences in the answers given by students, depending on the variables adopted to characterize the study group. Results: Based on the results of the factor analysis, it was confirmed that the age, gender, place of residence, educational level and source of income of the surveyed students have an impact on the employment choices they make. The conclusions resulting from the study are of cognitive and applicable nature, especially for employers and recruiters who, with this knowledge, can react flexibly and prepare accordingly to attract and hire employees from the generation “Z”.